Multi-System Deconditioning in 3-Day Dry Immersion without Daily Raise - De Abreu, Steven; Amirova, Liubov; Murphy, Ronan; Wallace, Robert; Twomey, Laura; Gauquelin-Koch, Guillemette; Raverot, Veronique; Larcher, Françoise; Custaud, Marc-Antoine; Navasiolava, Nastassia (Frontiers in Physiology, 2017)
Dry immersion (DI) is a Russian-developed, ground-based model to study the physiological effects of microgravity. It accurately reproduces environmental conditions of weightlessness, such as enhanced physical inactivity, suppression of hydrostatic pressure and supportlessness. We aimed to study the integrative physiological responses to a 3-day strict dry immersion protocol in 12 healthy men, and to assess the extent of multi-system deconditioning. We recorded general clinical data, biological data and evaluated body fluid changes. Cardiovascular deconditioning was evaluated using orthostatic tolerance tests (Lower Body Negative Pressure + tilt and progressive tilt). Metabolic state was tested with oral glucose tolerance test. Muscular deconditioning was assessed via muscle tone measurement. Results: Orthostatic tolerance time dropped from 27±1 min to 9±2 min after DI. Significant impairment in glucose tolerance was observed. Net insulin response increased by 72±23% on the third day of DI compared to baseline. Global leg muscle tone was approximately 10% reduced under immersion. Day-night changes in temperature, heart rate and blood pressure were preserved on the third day of DI. Day-night variations of urinary K+ diminished, beginning at the second day of immersion, while 24-h K+ excretion remained stable throughout. Urinary cortisol and melatonin metabolite increased with DI, although within normal limits. A positive correlation was observed between lumbar pain intensity, estimated on the second day of DI, and mean 24-h urinary cortisol under DI. In conclusion, DI represents an accurate and rapid model of gravitational deconditioning. The extent of glucose tolerance impairment may be linked to constant enhanced muscle inactivity. Muscle tone reduction may reflect the reaction of postural muscles to withdrawal of support. Relatively modest increases in cortisol suggest that DI induces a moderate stress effect. In prospect, this advanced ground-based model is extremely suited to test countermeasures for microgravity-induced deconditioning and physical inactivity-related pathologies.